Between Dewey, Social Movements and Critical Philosophy - Štěpán Raška (Filozofia)
This review study deals with the 2021 book by the Spanish philosopher Justo Serrano Zamora Democratization and Struggles against Injustice: A Pragmatist Approach to the Epistemic Practices of Social Movements. The aim is primarily to show how Zamora deals with Dewey’s thought in the context of social critical philosophy. At the same time, it highlights the value of Zamora’s approach both in the context of contemporary debates on democracy and in the context of reflections on the intrinsic connection between social movements and democratization. The reviewer simultaneously situates the book in the context of contemporary pragmatic philosophy and points out, among other things, the phenomenon of the gradual convergence of pragmatism with contemporary critical theory of society.